Midazolam in treatment of various types of seizures in children - Yakinci, C; Müngen, B; Sahin, S; Karabiber, H; Durmaz, Y (Elsevier Science Bv, 1997)
Midazolam is a recently developed water-soluble benzodiazepine that shares anxiolytic, muscle relaxant, hypnotic and anticonvulsant actions with other members of this class. There are limited studies that midazolam can be used successfully to treat seizures in adults and children. In this study, 0.2 mg/kg intramuscular (IM) midazolam was administered to 11 children (eight boys and three girls), aged 3 days to 4 years (mean age 1.8 +/- 1.4 years), with seizures of various types. In all but one child, seizures stopped in 15 s-5 min after injection. No side effects were observed. These results suggest that IM administration of midazolam may be useful in a variety of seizures during childhood, especially in case of intravenous (IV) line problem. (C) 1997 Elsevier Science B.V.
Keywords: midazolam; child; convulsion